A Study of Vowel Length in Olusuba. - Sande, Walter Ochieng; Ondondo, Emily Ayieta; Rew, Francis Owino (International Journal of English Language and Linguistics Research, 2019)
This article describes vowel length in Olusuba. The objective of this study is to investigate sources of vowel length in Olusuba. Data for this study was collected from a secondary source: Dholuo translation of Olusuba. A word list was generated and presented to native speakers of Olusuba who were instructed to read it loud while being recorded. The recorded data was then played back for phonetic transcription. Using a descriptive research design and basing on data generated from the secondary source and phonological realisation of the listed words by native speakers of Olusuba, there are two sources of vowel length in Olusuba: underlying vowel length and derived vowel length. This article describes the two sources. KEYWORD: , olusuba, phonological realisation, underlying, vowel length
Keywords: Derived; Olusuba; Phonological realisation; Underlying; Vowel length